New Approaches to Representation in Conceptual Design. (December 2014) - Serra, Pau de Solá-Morales
Design has been a human activity as long as humans are humans. In the last decades, a lot of academic research has been devoted to understand the theoretical and scientific bases on which this activity rests, and some of these aspects are beginning to be clear, in particular with respect to cognitive processes and representational needs. Therefore, in this article, we will: 1) briefly describe some current approaches to design thinking and in particular describe conceptual design; 2) analyze how current state-of-the-art software is neither designed to give an answer to these processes, nor to support conceptual design; and 3) introduce a new approach in the design of CAD software data models, so that conceptual design is better supported to truly "aid" designers in his praxis.